Endospanin Is a Candidate for Regulating Leptin Sensitivity - Londraville, Richard L.; Tuttle, Matthew; Liu, Qin; Andronowski, Janna M. (Frontiers in Physiology, 2022)
The hypothesis advanced is that endospanin, a highly conserved vesicle traffic protein in vertebrates, regulates leptin sensitivity in bone signaling. The effects of leptin on bones are well-studied but without consensus on whether the increases in leptin signaling stimulate bone gain or loss. The bone response may depend on leptin sensitivity, and endospanin is an established modulator of leptin sensitivity. An argument is advanced to develop zebrafish models for specific leptin signaling pathways. Zebrafish have well-developed molecular tools (e.g., CRISPR) and the advantage of non-destructive sampling of bones in the form of scales. Using these tools, experiments are described to substantiate the role of endospanin in zebrafish bone dynamics.